Desempenho agronômico e riscos fitossanitários associados a arranjos de plantas de soja no cerrado - Carmo, Eduardo Lima do (2015)
The Brazilian agricultural scenery goes through great transformations, in a tech point of view. Among several examples, there are the creation of new pesticide molecules, vegetables biotechnological manipulation, the development of high advanced machines, and the introduction of hard and fertile soybean cultivars. To the last, questionings are being surveyed about the type of management to be adopted as a way to improve the techniques of production, once they are plants of compact and upright architecture in which express more fertile potential and, for certain, have influence in the phytosanitary range. Towards the exposed, the execution of this work had as its goal, rate the development and productivity in soybean plants cultivated in different arrangements and the impact that it causes in the infestation, control and pests damages, as in the spray deposition of pesticides. It was conducted in two agricultural harvest between the years 2013 and 1015, trial fields composed of plants arrangements of soybean consisted in: traditional (0.5 m between the lines); crossed (0.5 m between the lines and 0.5 m between the lines in a perpendicularly way to the first); twin rows (0.25 m in couples tier and 0.75 m between the couple tiers) and narrow (0.25 m between the lines). The settled analysis was made, in which morphological and performance constituent characteristics, were rated. In the occasion, were made evaluate the infestation and caterpillar’s control and phytophagan chinch damages in beans too, as well as the spray deposition with the use of different methodologies. Referring the characteristics of plants development, there was an effect of year, as a centerpiece, the production to condensed arrangement, which is joined to the crossed, were superior to the number of caterpillar per area, once, observed the chinch damages, do not differ to the others treatments. The deposition of spray solution, both of methodologies were suitable as for the results, not showing difference between the arrangements. However, taxes of application of 75 and 150 L ha-1 were different as for volume of deposition spray solution in the inferior third of plants. Therefore, the development of the cultivars of soybean is conditioned to time variety, which may be interfering by the sowing arrangements, as well. Cconsidered the most advanced stage of development and the same plant population, arrangements with better spatial distribution are more favorable to caterpillars, but provides similar condition to phytosanitary control.